Prime Minister Decree No. 310 Of The Year 2014 Amending Presidential Decree No 284/1997 On The Establishment Of The General Authority For Investment And Free Zones = قرار رئيس مجلس الوزراء رقم 310 لسنة 2014 بتعديل القرار رقم 284 لسنة 1997 بإنشاء الهيئة العامة للاستثمار والمناطق الحرة - Egypt; The middle east library for economic services, translator. (2025)
Prime Minister Decree No. 310 of the year 2014 قرار رئيس مجلس الوزراء رقم 310 لسنة 2014